Impact of Heart Failure Team on Inpatient Rapid Sequencing of Heart Failure Therapy - Zhou, Zhongrui; Kardas, Khalid; Gue, Ying Xuan; Najm, Ali; Tirawi, Anas; Goode, Rachel; Frodsham, Robert; Kavanagh, Rory; Rao, Archana; Dobson, Rebecca; Wright, David; Kahn, Matthew (Journal of cardiovascular development and disease, 2025)
The management of heart failure (HF) has undergone a paradigm shift from conventional stepwise methods of initiation and the up-titration of HF therapy towards an early, more intensive initiation of pharmacotherapy to improve the prognosis. The aim of this study was to compare the outcomes of patients at the Liverpool Heart and Chest Hospital (LHCH), with new diagnosis of HF, who were reviewed by the inpatient heart failure team (HFT), compared to patients that were not reviewed. A retrospective review of the electronic records of patients admitted with a new diagnosis of HF to the LHCH from May to December 2023 was performed. Admission drugs were similar, apart from betablockers, which were more frequent in the non-HFT group (58% vs. 24.2%; p = 0.002). The length of inpatient stay was longer in the HFT group (median 5.5 days vs. 3 days; p = 0.001) and more likely to be on all four pillars of HF medical therapy (96.8% vs. 0; p < 0.001) within 30 days of discharge. The 30-day and 6-month mortality outcomes were not significantly different. Patients reviewed by the HFT were significantly more likely to receive the four pillars of HF therapy within 30 days of their diagnosis compared to their counterparts at the expense of a longer length of stay.